Utilization of Plastic Waste in the Concrete Industry - Sakr, Nancy Abdelmoneim (AUC Knowledge Fountain, 2026)
Plastic recycling has emerged as a crucial strategy that aligns with environmental, social and economic sustainability indicators. Currently, substantial volumes of plastic waste are either deposited in landfills or incinerated, neglecting the potential to harness its embodied energy and the energy consumed for producing virgin materials. A key advantage of plastic lies in its promising mechanical properties. Concrete mix design is fundamental to a wide range of construction applications, including brick walls, reinforced concrete slabs and concrete pavements. Despite the adoption of recycled plastic in construction materials in various countries, its widespread implementation remains limited. This is primarily due to the scarcity of experimental work in this area and the absence of a robust waste management system. This work underscores the importance of sustainable practices by exploring the utilization of recycled plastic within the global concrete industry. This work specifically investigates the reuse of two common types of plastic waste: polyethylene terephthalate (PET) and high-density polyethylene (HDPE) to mitigate plastic waste accumulation in landfills and enhance the performance of construction materials. The work investigates the use of recycled HDPE and PET as a replacement for coarse aggregates in concrete pavement mixtures. While recycled PET is more prevalent in concrete applications, recycled HDPE has demonstrated exceptional efficiency and durability. The recycling method used in this work is the mechanical recycling method due to its superior effectiveness in comparison with other methodologies. Thus, assessing the performance of recycled PET and HDPE in concrete pavement, aiming to diminish non-renewable energy consumption by 15-20%, curtail the carbon footprint by 15-30% and decrease plastic waste in landfills by 20-30% compared to conventional concrete. Also, the optimal recycled plastic within concrete to fall between 10% and 15%, as this range facilitates the attainment of the most desirable material properties.